PENGARUH FAKTOR INVESTASI, DIVIDEN DAN PROFIT TERHADAP NILAI PERUSAHAAN PERBANKAN YANG LISTED DI BURSA EFEK INDONESIA (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of investment decisions, dividends and profits on firmvalue. The research population is banking companies listed on the Indonesian Stock Foam(IDX) for the period 2014-2018. Investment decisions are proxied by the Price to Earning Ratio(PER); dividends are proxied by the Dividend Payout Ratio (DPR); Profit is proxied by Returnon Equity Ratio (ROE) and firm value is proxied by Price to Book Value (PBV). Data analysisused multiple linear regression which was processed by the SPSS program. The results showedthat investment decisions have a positive and significant effect on firm value. Dividend policyhas no effect on firm value. Profitability has a positive and significant effect on companyprofitability.Keywords: Investment Decisions, Dividend Policy, Profitability and Company Value